2020
DOI: 10.1016/j.brs.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity of the anterior cingulate cortex predicts treatment outcome for rTMS in treatment-resistant depression at 3-month follow-up

Abstract: Background and objective: Repetitive transcranial magnetic stimulation (rTMS) is a first-line treatment for treatment-resistant depression (TRD). The mechanisms of action of rTMS are not fully understood, and no biomarkers are available to assist in clinical practice to predict response to rTMS. This study aimed to demonstrate that after-rTMS clinical improvement is associated with functional connectivity (FC) changes of the subgenual cingulate cortex (sgACC) and rostral anterior cingulate (rACC), and FC of sg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 39 publications
3
46
1
4
Order By: Relevance
“…The present results suggest a dysfunctional pattern associated with depression that can be modulated bidirectionally (top-down/bottom-up), depending upon the precise location of the rTMS target. The present study reinforces first that small shifts in target location within DLPFC may produce large differences in outcome, and that alterations in rsfc patterns may be helpful both in selection of subjects and monitoring of response 20,21 .…”
Section: Discussionsupporting
confidence: 82%
“…The present results suggest a dysfunctional pattern associated with depression that can be modulated bidirectionally (top-down/bottom-up), depending upon the precise location of the rTMS target. The present study reinforces first that small shifts in target location within DLPFC may produce large differences in outcome, and that alterations in rsfc patterns may be helpful both in selection of subjects and monitoring of response 20,21 .…”
Section: Discussionsupporting
confidence: 82%
“…10,[44][45][46] However, fewer studies have reported a relationship between changes in RSFC and treatment response heterogeneity in TRD patients. 18,47,48 In this study, the seed-based exploratory analysis at baseline revealed a cluster that was associated with treatment response to ketamine within the AN, but not the DMN. This suggests that the AN plays a key role in treatment response in TRD with respect to the DMN in treatment-sensitive depression (TSD).…”
Section: Discussionmentioning
confidence: 61%
“…Albeit the results of many imaging studies support the sgACC as a critical region of MDD (Downey et al, 2016; Ho et al, 2014; Jaworska et al, 2014; Liu et al, 2015), including the FC findings of baseline sgACC‐DLPFC and sgACC‐left superior medial frontal gyrus connectivity predicted subsequent clinical improvement (Baeken et al, 2014; Cash et al, 2019; Fox et al, 2012; Ge, Downar, Blumberger, Daskalakis, & Vila‐Rodriguez, 2020; Liston et al, 2014; Weigand et al, 2018), there have a lot of evidences supporting the pgACC as a critical region of MDD (Ball, Stein, & Paulus, 2014; Boes et al, 2018; Pizzagalli, 2010; Silverstein et al, 2015; Zhou et al, 2017), and pgACC has been reported to show higher FC with the left lateral parietal cortex (IPL) at baseline in better clinical response group (Ge et al, 2020). In view of the above FC‐based researches, the current study investigated the ACC‐DLPFC FC as well as its association with rTMS efficacy.…”
Section: Discussionmentioning
confidence: 99%